2022
DOI: 10.1108/ijcma-07-2022-0121
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational politics and workplace gossip: the moderating role of compassion

Abstract: Purpose This study aims to examine perceived organizational politics (POP) as an antecedent to workplace gossip. While the commonly held belief is that POP is consequential to the existence of negative workplace gossip, an alternate hypothesis can be that POP may predict positive workplace gossip as well. The study further explores the role of compassion as a boundary condition in the relationship of POP with negative and positive valences of workplace gossip. Design/methodology/approach Using purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Employees who are forcibly asked to devote extra energy enhance citizenship fatigue among employees (De Clercq et al, 2021). According to the COR theory, employees continually want to acquire new resources, as they have limited resources (Khan et al, 2023e;Moon and Morais, 2022). If they are unsuccessful, then they are more likely to suffer unfavorable consequences (Chen et al, 2023;Haider and Yean, 2023).…”
Section: Organizational Citizenship Behaviors and Work-life Conflict ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Employees who are forcibly asked to devote extra energy enhance citizenship fatigue among employees (De Clercq et al, 2021). According to the COR theory, employees continually want to acquire new resources, as they have limited resources (Khan et al, 2023e;Moon and Morais, 2022). If they are unsuccessful, then they are more likely to suffer unfavorable consequences (Chen et al, 2023;Haider and Yean, 2023).…”
Section: Organizational Citizenship Behaviors and Work-life Conflict ...mentioning
confidence: 99%
“…From the COR perspective, when employees invest their valuable resources, they tend to have the feeling that their resources are not lost or that further depletion of resources is prevented (Khan et al, 2023e;Zhang et al, 2023); thus, negative consequences are reduced. Similarly, individuals who have such personality traits will face lower levels of citizenship fatigue, as they either work excessively or compulsively (Ong and Kou, 2023), and such a personality aspect serves as a resource for them (Alqhaiwi and Luu, 2023), which prevents the negative consequences of work-family conflict.…”
Section: Workaholism As a Moderatormentioning
confidence: 99%
“…In response, employees become more likely to gossip (Houmanfar and Johnson, 2004). Empirical research has shown that organizational gossip is associated with anger and shame (Zong et al , 2023), perceived organizational politics, compassion (Khan and Chaudhary, 2023), employees’ mental health and psychological capital (Cheng et al , 2023). Organizational gossip has a negative relationship with organizational identity (Xie et al , 2022) and threat to self-respect and a positive relationship with supervisor civility and psychological distress (Ye et al , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Thus, employees who are harmed by gossip can be expected to reciprocate through revenge. Empirical research on organizational gossip has focused on the effects such as perceived organizational politics (Khan and Chaudhary, 2023), such premises as revenge, organizational citizenship behavior (Martinescu et al , 2021), organizational identity (Ye et al , 2019), job engagement and burn out (Georganta et al , 2014). However, almost no studies have examined how employees react to negative gossip.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, more than half of the reviewed studies explored the consequences of workplace gossip (e.g., [66,127]), and only about a quarter of the studies examined antecedents of workplace gossip (e.g., [44,56]). Most studies used either time-lagged (e.g., [71,103]) or cross-sectional designs (e.g., [69,115]).…”
Section: Review Findingsmentioning
confidence: 99%